Automated Feedback Effect on Foreign Language Writing Motivation and Anxiety - ALTINAY, GÜLNİHAN; Aydın, Selami (IGI Global, 2025)
Writing motivation, anxiety, and feedback play significant roles in enhancing or debilitating writing performance, while automated feedback, offering immediate and personalized responses, can help reduce anxiety and increase motivation. This study examines the effects of traditional teacher feedback versus automated feedback on EFL learners' writing motivation and anxiety. Using a quasi-experimental design, 26 first-year English as a foreign language (EFL) students participated. Data were collected through a demographic questionnaire, the Academic Writing Motivation Questionnaire (AWMQ), and the Second Language Writing Anxiety Inventory (SLWAI). Over four weeks, the control group used pen and paper, while the experimental group used Write & Improve. The study concluded that teacher feedback positively impacted writing motivation and anxiety, while automated feedback reduced anxiety but decreased motivation. It is recommended that automated feedback should be balanced with teacher feedback to reduce anxiety and maintain motivation in EFL learners. © 2026 by IGI Global Scientific Publishing. All rights reserved.
AI's Role in Language Learning and Communication
Source Title: AI's Role in Language Learning and Communication.
Keywords: Feedback; Motivation; Paper; Population statistics; Teaching